"What do the Papers Say?” How Press Reviews Link National Media Arenas in Europe - Erbe, Jessica (Javnost-The Public, 2005)
Numerous empirical studies have measured to what degree national mass media arenas in Europe converge in terms of news agendas, ways of framing, and reporting political claims from other countries or EU actors. This article suggests explaining such outputoriented findings with a theoretical model of mechanisms that link different mass media arenas. It is derived from national settings, where mass media arenas are also highly fragmented and yet sufficiently interlinked to be considered a public sphere. The most prominent mechanism is news agencies providing similar input to many arenas. The article draws attention to an under-investigated mechanisms of cooperation, mutual observation, and inter-referencing between different media outlets. Empirical evidence about press reviews in several European countries is presented here for the first time. The daily practice of radio stations, newspapers, or websites, to explicitly quote commentaries or news from other media is found to be a routine in many countries, and it often crosses national borders. The results suggest that the ‘opinion geography’ of press reviews differs from the usual .news geography. in European media, frequently entailing a Europeanised perspective on whose views are seen as relevant.